ANALYSIS OF BUSINESS SUCCESS FOR KENDANG CRAFTS IN THE CITY OF BLITAR - Immanuel Ustradi Osijo; Sudarmiatin; Agus Hermawan (Badan Penerbit STIEPARI Press, 2022)
The existence of MSMEs is the backbone of the community's economy which is important in growing the economy of a region. In this regard, education and training are continuously held in all fields to create reliable, skilled, and competent entrepreneurs. The purpose of this study was to determine efforts to increase business success by cultivating entrepreneurial character, entrepreneurial attitude, and entrepreneurial education for kendang craftsmen in Blitar City. This research is a qualitative single case study. The research method uses full observation or observation, in-depth interviews, and documentation. The results showed that the entrepreneurial characteristics of Kendang Craftsmen were having entrepreneurial characteristics of trust, thirst for achievement, independence, optimism, profit or result-oriented, painstaking hard work, tenacity, persistence, disciplined, diligence, and ability to take risks. The entrepreneurial attitude developed by Kendang Craftsmen shows an honest attitude in acting, high discipline, self-confidence, responsibility, innovation, sociable, kind, friendly, smart, selective, and does not discriminate against people. The Entrepreneurship Education conducted by Kendang Craftsmen is different. Education can be obtained from three types of education, namely formal, non-formal and informal education